A intervenção da terapia ocupacional associada a estimulação transcraniana por corrente contínua em pessoas com a síndrome dolorosa miofascial: efeitos na dor, qualidade de vida, desempenho e papéis ocupacionais - Marchi, Letícia Zanetti (Universidade Federal de São Carlos, 2022)
Myofascial pain syndrome (MPS) is a specific clinical condition of regional muscle pain, very often associated with the presence of one or more tender points, which in these circumstances are called trigger points. Many techniques and types of multimodal treatment have been used, showing good results. This study aims to investigate the effects of Transcranial Direct Current Stimulation combined with Occupational Therapy on the primary outcome pain. Therefore, a multiple case study with an experimental approach was adopted as a method. In which the participants were referred by neurologists and previously diagnosed. Participants were screened (Hamilton Anxiety Scale and Beck Depression Inventory instruments), initial assessment (Visual Analog Pain Scale and Body Map instruments, Mc Gill Pain Questionnaire, Canadian Occupational Performance Measure, Occupational Role List and World Health Organization quality of life instrument - abbreviated), intervention (3 times a week, 30 minutes, 12 sessions) and final assessment. Participants were randomly divided into two groups, an Occupational Therapeutic Intervention (OT) group and an Occupational Therapy and Transcranial Direct Current Stimulation (tDCS+OT) group. The results show that all participants are female, most have pain in the cervical region or close to this area. It is also observed that the participants have difficulty in occupational performance in the items self-care and productivity. In the primary outcome pain in both the right and left hemibody, the target participants of the OT intervention only had better results, in the change of the pain level and also in the pain intensity. In the secondary outcome quality of life, all participants improved, but participants in the tDCS plus OT group had a better mean score when comparing pre- and post-intervention outcomes than participants in the OT only group. In the secondary outcome occupational performance, all participants improved their scores in both satisfaction and performance, but the participants who had a change in score of 2 points or more considered as clinically significant by the COPM instrument were: 1 participant in the tDCS group plus TO and 2 participants in the TO-only group. It can be concluded from the analysis of the results that both an intervention (tDCS plus OT) and another (only OT) were beneficial to their participants, but that in this scenario the OT only group had better scores in more predicted outcomes (pain and functional performance). In addition, the study could be carried out with a larger number of participants so that it is possible to generalize the results and validate the protocol built for the intervention of OT, as well as, perhaps, confirm that tDCS is an adjuvant and potentiating technique for the TO. The innovative character of the theme for the Occupational Therapy profession is highlighted, in relation to SDM and one of the interventions made - tDCS.
Occupational therapy intervention associated with transcranial direct current stimulation in people with myofascial pain syndrome: effects on pain, quality of life, performance and occupational roles
Keywords: Terapia ocupacional; Síndrome Dolorosa Miofascial; Estimulação transcraniana por corrente contínua; Occupational therapy; Miofascial pain syndrome; Transcranial direct current stimulation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL